Land Comprehensive Carrying Capacity of Major Grain-Producing Areas in Northeast China: Spatial–Temporal Evolution, Obstacle Factors and Regulatory Policies - Gao, Jia; Zhao, Rongrong; Zhan, Yuxin (Sustainability, 2022)
Major grain-producing areas in Northeast China serve as a significant national commodity in their role as grain bases. In order to achieve sustainable land use in such areas and ensure national food security, it is critical to understand the spatial–temporal evolution features of the land comprehensive carrying capacity of such areas, ascertain major obstacle factors and propose regulatory policies for effectively improving the land comprehensive carrying capacity. In this paper, a TOPSIS model based on grey relational entropy weight is developed to analyze the spatial–temporal evolution features of the land comprehensive carrying capacity of major grain-producing areas in Northeast China from 2000 to 2020, and an obstacle degree model is employed to determine the main obstacles to improving the land comprehensive carrying capacity of major grain-producing areas in Northeast China. The study results show the following: (1) The land comprehensive carrying capacity of major grain-producing areas in Northeast China is at a low level, showing an N-shaped trendline, and its spatial–temporal evolution features are subject to changes in land food carrying capacity, land economic carrying capacity and land ecological carrying capacity.(2) The main obstacle factors for improving the land comprehensive carrying capacity of major grain-producing areas in Northeast China are urbanization rate, gross industrial output per hectare and industrial solid waste emission per hectare. Cultivated land area per capita, grain output per hectare and industrial wastewater discharge per hectare have recently become obstacle factors for the land comprehensive carrying capacity of the study areas. Based on these results, the paper proposes regulatory strategies for stabilizing agricultural population transfer to avoid its reversal, exploring the optimization and upgrading of secondary sector structures to promote a low-carbon transition to green industries, and implementing cultivated land protection policies to steadily boost cultivated land grain productivity, with a view to increasing the land comprehensive carrying capacity of major grain-producing areas in Northeast China. The findings of this study act as a scientific reference for enhancing the land comprehensive carrying capacity of major grain-producing areas in Northeast China, which is crucial for ensuring national food security.